Prodromus of a fern flora for Bolivia. II. Lycopodiaceae - Øllgaard, Benjamin; Kessler, Michael; Smith, Alan R. (Phytotaxa, 2018)
We provide a synopsis to the family Lycopodiaceae in Bolivia, including 40 species (some with varieties) in eight genera. One new species, Phlegmariurus stephani B.Øllg., is described. Keys are given to genera and species. Most relevant synonyms are mentioned, the general and Bolivian distribution and ecology is summarized, and some notes on related species are given.